PENGARUH MODEL KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK - Nova Vella; Abdussamad Abdussamad; Suparjan Suparjan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The problem with this study is "Is there an influence of make a match type cooperative model on students' learning outcomes in thematic learning?". This research aims to describe how highly the influence of make a match-type cooperative models affects students' learning outcomes in thematic learning. This research uses experimental methods. Collection technique is a measurement technique while the data collection tool is a written test in the form of multiple choice which amounts to 50 questions. Based on statistical calculations the average results of post-test class control studies were 77.31 and the average post-test experiment class was 81.43. Hypothetical test results using t-test obtained thitung = 2,521 for dk = 68 and a=5% obtained ttabel = (1,67) which means thitung ( 2,521) < ttabel (1.67), then Ha accepted. It can be concluded that there is an influence of make a match type learning model on students' learning outcomes in Thematic Learning. From the calculation of effect size (ES) obtained ES amounted to 0.53 in the moderate category. It can be said that the cooperative model of Make a Match type has a considerable influence on students' learning outcomes in Thematic Learning. Keywords :Influence, Make a Match Type,Learning Results, Thematic.